Pengaruh Jam Kerja Lembur dan Leader Member Exchange (LMX) terhadap Turnover Intention Karyawan Departement Finishing PT. Ungaran Sari Garments - Silfiati Rohmah; Yunita Primasanti; Agung Widiyanto Fajar Sutrisno (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Turnover intention is the tendency or intention of individuals to leave the organization for various reasons, one of which is the desire to get a better job. This study aims to examine the effect of overtime working hours and leader member exchange on turnover intention of finishing department employees of PT Ungaran Sari Garments. The sample taken was 144 finishing department employees. The sampling technique used the slovin formula with data analysis techniques, namely multiple linear regression using the SPSS 25 program. The results obtained that overtime working hours have a positive and significant effect on turnover intention, while lmx has a negative and significant effect on turnover intention. overtime working hours and leader member exchange have a simultaneous or joint effect on the dependent variable, namely turnover intention of pt usg finishing department employees.